LITERATURE REVIEW ON WATERMARKING TECHNIQUES OF RELATIONAL DATABASES - KANCHAN S. RAHINJ, (International Journal of Innovations in Engineering Research and Technology, 2021)
Watermarkingis commonly used technique in which, information is enforced to prove ownership on different types of data such as image, audio, video, text and relational database. There are many watermarking techniquesfor databases. These paper describe, History of watermarking, Applications of digital watermark for relational databases, Types of attacks on watermark database, and most important existing watermarking techniques. Social network data are being mined for extracting knowledgeable patterns. Such data are composed by different researchers and organizations and this are usually also shared via different channels. These data is usually big in volume because there are millions of social network users all over the world. In this context, ownership protection of such data with huge volume becomes relevant. Digital watermarking is a more demanding solution than any other technique for ensuring rights protection and integrity of the original data sets. The objective of this paper is to study work done in watermarking on relational data until now.